The Role of Preoperative 18F-fluorodeoxyglucose Positron Emission Tomography/Computed Tomography in Retroperitoneal Sarcoma - Jo, Sung Jun; Kim, Kyeong Deok; Lim, So Hee; Kim, Jinseob; Hyun, Seung Hyup; Park, Jae Berm; Lee, Kyo Won (Frontiers in Oncology, 2022)
18F-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) was used to predict pathologic grades based on the maximum standardized uptake value (SUVmax) in soft tissue sarcoma and bone sarcoma. In retroperitoneal sarcoma (RPS), the effectiveness of PET was not well known. This study was designed to investigate the association of SUVmax with histopathologic grade and evaluate the usefulness of 18F-FDG PET/CT before operation. Patients at Samsung Medical Center undergoing primary surgery for retroperitoneal sarcoma with preoperative 18F-FDG PET/CT imaging between January 2001 and February 2020 were investigated. The relationship between SUVmax and histologic features was assessed. The association of SUVmax with overall survival (OS), local recurrence (LR), and distant metastasis (DM) were studied. Of the total 129 patients, the most common histologic subtypes were liposarcoma (LPS; 68.2%) and leiomyosarcoma (LMS; 15.5%). The median SUVmax was 4.5 (range, 1- 29). Moreover, SUVmax was correlated with tumor grade (p < 0.001, Spearman coefficient; 0.627) and mitosis (p < 0.001, Spearman coefficient; 0.564) and showed a higher value in LMS (12.04±6.73) than in dedifferentiated liposarcoma (DDLPS; 6.32±4.97, p = 0.0054). SUVmax was correlated with pathologic parameters (tumor grade and mitosis) in RPS and was higher in the LMS group than the DDLPS group. The optimal SUVmax threshold to distinguish high tumor grade was 4.8. Those with a SUVmax greater than the threshold showed poor prognosis regarding OS, LR, and DM (p < 0.001).